Performance measurement in library and information services of Makati City Library - Tomas, Roselyn D. (School of Library and Information Studies, University of the Philippines Diliman, 2008)
The use of performance measurement for public libraries is done to gain insight into, and make judgments about the effectiveness and efficiency of programs, processes, and people. The measurement of performance makes use of indicators that measure a library's progress in meeting strategic goals and objectives, gather and analyze performance data, and then use these data to drive improvements in the organization and successfully translate strategy into action.